The Impact of Digital Technologies on the Development of Payment Services - A. Y. Chentsov (Цифровая трансформация)
The article reveals the system of functioning of payment services as a financial institution, the emergence and development of which is due to scientific and technical progress at the present stage of development and considering the impact of globalization. This tool occupies an increasingly high share of the financial sphere, but due to the novelty of electronic systems, this topic is currently little studied. The article considers the latest developments that allow you to make instant payments conveniently and safely. The problems and ways of protecting user identification, data privacy and money safety when using electronic payment services are investigated. The study revealed that, along with innovative global developments, to strengthen the electronic payment system, it is necessary to implement common international standards for combating cybercrime.